Mosque Management and Economic Empowerment Through Sukuk Based Investment - Saheedadewale Badmus; Abioye Abdulwaliu (Al-Fadilah: Islamic Economics Journal, 2026)
This paper examines the financial sustainability of mosques in Nigeria, highlighting their historical role as centers of education, social welfare, and community development. Despite these roles, many mosques remain financially fragile due to overreliance on irregular individual donations and special levies. Using a qualitative research approach with descriptive and analytical methods, the study explores how Sukuk-based investments can enhance mosque management and economic empowerment. The paper argues that adopting modern management techniques alongside Sukuk financing can revitalize mosque funding structures and reduce dependency on traditional donation models. Findings reveal that integrating Sukuk enables mosques to shift from passive recipients of charity to active participants in ethical and sustainable economic activities. The study concludes that achieving mosque financial sustainability is vital for promoting social welfare and economic emancipation within communities. It recommends incorporating Sukuk-based investment models into contemporary mosque management to build resilient, self-sustaining institutions capable of contributing meaningfully to holistic community development.